ANALISIS PENGARUH PENDIDIKAN DAN LATIHAN, MOTIVASI, KEPUASAN KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT IBU DAN ANAK ERIA BUNDA - PEKANBARU - Imran Imran (Ensiklopedia of Journal, 2020)
RSIA Eria Bunda is a privately owned type-C mother and child hospital located in Pekanbaru, Riau. This hospital provides services in the field of special health for mothers and children supported by specialist doctor services and supported by other medical facilities. The scope of health services provided by RSIA Eria Bunda Pekanbaru include emergency services, outpatient polyclinics, pharmaceutical installations, inpatients, HCUs, ICUs, NICUs, PICUs, nutrition installations, laboratories and other medical support. This research aims to Analyze The Influence Of Education And Training, Motivation, Satisfaction Work Against Nurse Performance At Mother And Children’s Eria Bunda Hospital In Pekanbaru. The research method used in this study is a descriptive method using qualitative data analysis, as well as data analysis by connecting between the theory and the problem under study. The research results obtained are: (1) education and training, motivation and job satisfaction do not have a positive influence on nurse performance by superiors, (2) education and training, motivation and job satisfaction have a positive effect on nurses 'own performance, (3) education and training have a positive influence on nurses' own performance, (4) motivation has a positive influence on nurses 'own performance, and (5) job satisfaction has a positive effect on nurses' own performance. The conclusion in this study is education and training, motivation and job satisfaction do not have a positive influence on nurse performance by superiors, education and training, motivation and job satisfaction have a positive effect on nurses' own performance, motivation has positive influence on the performance of nurses themselves, satisfaction has a positive effect on the performance of nurses themselves. The use of multiple linear regression analysis provides a good regression model for the nurse's own performance response variable.